Efecto de secuencias de sismos en la probabilidad de daño de edificios porticados de concreto armado en el Perú. - Emersson Baltazar, A.H. (2025)
Peru, exposed to recurrent earthquakes, faces challenges in the structural safety of its buildings due to the aftershocks that follow the main seismic events. In this article, the effect of earthquake sequences on a typical reinforced concrete porticoed building of educational infrastructure in Peru was studied with the objective of estimating the variation in the expected probability of damage. The methodology followed has consisted of the estimation of fragility curves by means of incremental dynamic analysis (IDA) under a series of seven single earthquakes and the effect of seven subsequent earthquakes. To simulate the behavior under the sequence of earthquakes, four incremental initial damage conditions have been established: fully operational (ND), immediate occupancy (IO), life safety (LS) and prevention of collapse (CP); based on the safety limit states of the building estimated by pushover analysis. The demand parameter used was the maximum interstory drift (MID) and the intensity parameter, the maximum ground acceleration (PGA). The obtained fragility curves have been compared to estimate the effects that subsequent earthquakes have on the probability of damage. The results conclude that the sequence of earthquakes increases the probability of expected damage compared to a single earthquake, from 5% to 35% and from 17% to 59% in the X-X and Y-Y directions respectively. This research demonstrates the importance of considering successive earthquakes in seismic analyses and provides a basis for discussion for Peruvian earthquake-resistant regulations.